ELECTIONS TO THE EUROPEAN PARLIAMENT IN LITHUANIA: „NATIONAL“ AND „EUROPEAN“ CAMPAIGNING TOPICS - Mazylis, Liudas; Unikaite-Jakuntaviciene, Ingrida; Povilaitis, Romualdas; Mazylyte, Liucija (European Scientific Journal, ESJ, 2015)
Elections to the EP held in Lithuania 2004, 2009, 2014 are analysed with special attention to the latter ones. Content analysis of party programs and of news media portal texts was carried out combining with individual level data. Positions of interest groups were taken into account as well. Meeting criteria of „second order“ elections are discussed.